Inherent Impurities in Graphene/Polylactic Acid Filament Strongly Influence on the Capacitive Performance of 3D-Printed Electrode - Ghosh, Kalyan; Ng, Siowwoon; Iffelsberger, Christian; Pumera, Martin (Chemistry - A European Journal, 2020)
Additive manufacturing or 3D-printing have become promising fabrication techniques in the field of electrochemical energy storage applications such as supercapacitors, and batteries. Of late, a commercially available graphene/polylactic acid (PLA) filament has been commonly used for Fused Deposition Modeling (FDM) 3D-printing in the fabrication of electrodes for supercapacitors and Li-ion batteries. This graphene/PLA filament contains metal-based impurities such as titanium oxide and iron oxide. In this study, we show a strong influence of inherent impurities in the graphene/PLA filament for supercapacitor applications. A 3D-printed electrode is prepared and subsequently thermally activated for electrochemical measurement. A deep insight has been taken to look into the pseudocapacitive contribution from the metal-based impurities which significantly enhanced the overall capacitance of the 3D-printed graphene/PLA electrode. A systematic approach has been shown to remove the impurities from the printed electrodes. This has a broad implication on the interpretation of the capacitance of 3D-printed composites.
CRIS-Team Scopus Importer:2022-11-02
Keywords: 3D-printing; energy storage; graphene/PLA; impurities; supercapacitors